EUGLYCAEMIC DIABETIC KETOACIDOSIS (DKA) IN A 21-YEAROLD PATIENT ON SGLT-2 INHIBITO - Tan, Khai Tong (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION A 21-year-old lady with Type 2 Diabetes Mellitus for 2 years was on Empagliflozin, Linagliptin and Metformin for 10 months. She developed Euglycaemic Ketoacidosis after voluntarily going on a low carbohydrate diet for 3 days. CASE The patient was diagnosed to have Type 2 Diabetes Mellitus in 2016. She was well but not compliant with diet control. In Dec 2018, she was noted to have HbA1c of 9.3% and fasting Triglyceride was 13.06 mmol/L. For 3 days she decided to have a strict low calorie and low carbohydrate diet. She developed nausea and vomiting and was found to be in ketoacidosis. Euglycaemic Ketoacidosis was confirmed by blood glucose of 6.3 mmol/L; urine ketone positive 3+; blood ketone high; lactic acid normal; bicarbonate less than 10 mmol/L. She recovered after treatment with dextrose / insulin infusion. CONCLUSION More vigilance is required for patients on SGLT-2 inhibitors who may have to undergo fasting or periods of reduced food intake eg after surgery or procedures.